Exploring a potential mechanistic role of DNA methylation in the relationship between in utero and post‐natal environmental exposures and risk of childhood acute lymphoblastic leukaemia. Issue 11 (19th March 2019) - Timms, Jessica A.; Relton, Caroline L.; Sharp, Gemma C.; Rankin, Judith; Strathdee, Gordon; McKay, Jill A.
Abstract : The aetiology of childhood acute lymphoblastic leukaemia (ALL) is unclear. Genetic abnormalities have been identified in a number of ALL cases, although these alone are not sufficient for leukaemic transformation. Various in utero and post‐natal environmental exposures have been suggested to alter risk of childhood ALL. DNA methylation patterns can be influenced by environmental exposures, and are reported to be altered in ALL, suggesting a potential mediating mechanism between environment and ALL disease risk. To investigate this, we used a 'meet in the middle' approach, investigating the overlap between exposure‐associated and disease‐associated methylation change. Genome‐wide DNA methylation changes in response to possible ALL‐risk exposures (i.e. breast feeding, infection history, day care attendance, maternal smoking, alcohol, caffeine, folic acid, iron and radiation exposure) were investigated in a sub‐population of the Avon Longitudinal Study of Parents and Children (ALSPAC) cohort using an epigenome‐wide association study (EWAS) approach (n = 861–927), and compared to a list of ALL disease‐associated methylation changes compiled from published data. Hypergeometric probability tests suggested that the number of directionally concordant gene methylation changes observed in ALL disease and in response to the following exposures; maternal radiation exposure ( p = 0.001), alcohol intake ( p = 0.006); sugary caffeinated drink intake during pregnancy ( p = 0.045); and infant day care attendance ( p = 0.003), were not due to chance. Data presented suggests that DNA methylation may be one mediating mechanism in the multiple hit pathway needed for ALL disease manifestation. Abstract : What's new? In utero and post‐natal environmental exposures have been suggested to play a role in childhood acute lymphoblastic leukaemia (ALL) alongside genetic abnormalities. The aetiology of the disease however remains unclear. Here, the authors investigated whether environmental exposures associated with increased ALL risk influence changes in DNA methylation patterns in offspring, and potential concordance with methylation changes in ALL disease. They found statistically significant directionally concordant changes in methylation for maternal radiation exposure, alcohol or sugary caffeinated drink intake, and childhood daycare attendance. DNA methylation may play a mediating role in the causal pathway linking ALL risk exposures with disease risk.